Cultivating a Jewish Eco- Education Framework: The Toronto Heschel School’s Teaching and Learning Garden - Nadine Ijaz; Paige Mawson (Canadian Jewish Studies / Études juives canadiennes, 2021)
Over the last century, global food systems have increasingly shifted towards a scientific, input-based industrial paradigm whose adverse ecological impacts are well documented. In response, global agricultural movements, such as the agroecology movement, have sought an integration of contemporary science and indigenous agricultural knowledges. Scholars in the field of Jewish ecology similarly propose that biblical Hebrew scripture may provide a framework for thinking about, and acting upon, issues of ecological sustainability in agriculture. In educational settings too, learning about ecology is increasingly approached in an intimate and tangible way in the form of school garden programs. In this work, we highlight the case of the Toronto Heschel School, a Canadian Jewish day school for children in which a Teaching and Learning Garden fosters student learning on ecology and their Jewish identity in tandem. Reporting the thematic results of qualitative interviews with two educators and five alumni from the Heschel School, this study highlights key similarities and differences between this school’s garden program and those taking place in secular school settings. Like secular school gardens, the Heschel program implements experiential, interdisciplinary learning activities within a scientific ecological knowledge (SEK) framework. That said, the Heschel program supplements and deepens these SEK activities with traditional ecological knowledge (TEK) rooted in Judaic traditional teachings. The resulting educational outcomes appear at once universally applicable while specifically relevant to the Jewish identities of learners.